Ring-enhancing spinal cord lesions in neuromyelitis optica spectrum disorders. Issue 3 (2nd December 2016) - Zalewski, Nicholas L; Morris, Padraig P; Weinshenker, Brian G; Lucchinetti, Claudia F; Guo, Yong; Pittock, Sean J; Krecke, Karl N; Kaufmann, Timothy J; Wingerchuk, Dean M; Kumar, Neeraj; Flanagan, Eoin P
Abstract : Objective: We assessed the frequency and characteristics of ring-enhancing spinal cord lesions in neuromyelitis optica spectrum disorder (NMOSD) myelitis and myelitis of other cause. Methods: We reviewed spinal cord MRIs for ring-enhancing lesions from 284 aquaporin-4 (AQP4)-IgG seropositive patients at Mayo Clinic from 1996 to 2014. Inclusion criteria were as follows: (1) AQP4-IgG seropositivity, (2) myelitis attack and (3) MRI spinal cord demonstrating ring-enhancement. We identified two groups of control patients with: (1) longitudinally extensive myelopathy of other cause (n=66) and (2) myelitis in the context of a concurrent or subsequent diagnosis of multiple sclerosis (MS) from a population-based cohort (n=30). Results: Ring-enhancement was detected in 50 of 156 (32%) myelitis episodes in 41 patients (83% single; 17% multiple attacks). Ring-enhancement was noted on sagittal and axial images in 36 of 43 (84%) ring enhancing myelitis episodes and extended a median of two vertebral segments (range, 1–12); in 21 of 48 (44%) ring enhancing myelitis episodes, the ring extended greater than or equal to three vertebrae. Ring-enhancement was accompanied by longitudinally extensive (greater than or equal to three vertebral segments) T2-hyperintensity in 44 of 50 (88%) ring enhancing myelitis episodes. One case of a spinal cord biopsy during ring-enhancing myelitis revealed tissue vacuolation and loss of AQP4 immunoreactivity with preserved axons. The clinical characteristics of ring-enhancing myelitis episodes did not differ from non-ring-enhancing episodes. Ring-enhancing spinal cord lesions were more common in NMOSD than other causes of longitudinally extensive myelopathy (50/156 (32%) vs 0/66 (0%); p≤0.001) but did not differ between NMOSD and MS (50/156 (32%) vs 6/30 (20%); p=0.20). Conclusions: Spinal cord ring-enhancement accompanies one-third of NMOSD myelitis episodes and distinguishes NMOSD from other causes of longitudinally extensive myelopathies but not from MS.